Challenges of the Hyogo framework for action in the disaster relief response and early recovery in the a municipality in Cebu, Philippines, in the aftermath of Super Typhoon Yolanda (International Name Haiyan) - Corro, Liza D. (2016)
Responding to the need to create a sustainable framework on disaster relief response, this study aims to assess the Relief Distribution and Early Recovery efforts in the Municipality of Daanbantayan, Cebu after Super-typhoon Yolanda using the Hyogo Framework for Action (HFA). It also aims to propose a policy on Disaster Relief Response and Early Recovery Mechanism for the Philippines. It used the qualitative approach through key informant interviews. Findings show challenges encountered in the relief distribution and early recovery efforts. The Daanbantayan Municipality used the freewheeling mode of distribution, which means there was an absence of the desired policy. The gap between policies escalated to other adverse events, like the lack of coordination among humanitarian agencies with the local government unit of Daanbantayan and the lack of trust among main players in the management of distribution. These were manifested in the uneven distribution of relief goods, provision of some inappropriate relief goods, rise of security and economic issues, excessive relief goods in some barangays , mendicancy tendencies, inaccurate media reports, relief goods held at the airport due to Bureau of Customs issues, and politicking among local and national government officials. These findings recommend the following : (1) the endorsement of the proposal to strengthen the implementation of the disaster relief and recovery laws; and (2) the drafting of a proposal of national policies for the implementation of Disaster Relief Recovery Guidelines and the immediate application of penal clauses provided in the NDRRM law to discourage fraud and demand accountability from government officials and others who violate pertinent laws.
Keywords: Humanitarian assistance; Emergency management; Disaster relief; Super Typhoon Yolanda, 2013